The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5539/elt.v6n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Iranian EFL Students’ Foreign Language Anxiety, Foreign Language Listening Anxiety and Their Listening Comprehension

Abstract: Anxiety is an influential factor in a foreign language learning domain and plays a crucial role in language learners' performance. The following study was conducted to explore the possible impact of Foreign Language Anxiety and Foreign Language Listening Anxiety on language learners' listening skill. The researcher was interested to know the correlation that could exist among the three variables: Listening Comprehension, Foreign Language Anxiety and Foreign Language Listening Anxiety. The participants of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 39 publications
(52 reference statements)
4
40
1
Order By: Relevance
“…Concerning the receptive skills, Serraj & Noordin (2013) found that the relationship between foreign language anxiety and foreign language listening anxiety of the participants are in accordance with each other. Golchi (2012) found that listening anxiety had negative correlation with listening comprehension and female learners were more anxious than male learners.…”
Section: The Impact Of Fl Anxiety On Language Proficiencysupporting
confidence: 61%
See 1 more Smart Citation
“…Concerning the receptive skills, Serraj & Noordin (2013) found that the relationship between foreign language anxiety and foreign language listening anxiety of the participants are in accordance with each other. Golchi (2012) found that listening anxiety had negative correlation with listening comprehension and female learners were more anxious than male learners.…”
Section: The Impact Of Fl Anxiety On Language Proficiencysupporting
confidence: 61%
“…Yahya, 2013;Chiang, 2012), and listening (e.g. Baran-Lucarz, 2013;Serraj & Noordin, 2013). These studies were conducted in different contexts, and their results showed conflict findings.…”
Section: Introductionmentioning
confidence: 95%
“…The findings, in addition to giving us insight on the nature of a variable like anxiety, may justify the necessity of further studies. Although some researchers indicated that there is a positive correlation between FLCA and oral English test achievement (Lian & Budin, 2014), FLCA is negatively correlated with reading (Wu, 2011), writing (Tallon, 2014), listening (Serraj & Noordin, 2013), and speaking (Tóth, 2012) skills. Therefore, teachers should familiarize the students with SRLSs and accentuate their positive effects on language skills and notify that by employing SRLSs they can not only enhance their learning but also reduce their level of language anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Although these two concepts were rather investigated separately, there has been a growing interest in exploring the relationship between FL listening anxiety and FL listening comprehension strategy use (Gönen, 2009;Golchi, 2012;Xu, 2013;Serraj & Noordin, 2013;Han, 2014;Moghadam & Ghanizadeh, 2015). Studies in this vein seek to explore the existence of a possible relationship from different perspectives in various EFL contexts.…”
Section: Fl Listening Comprehension Strategies and Fl Listening Anxietymentioning
confidence: 99%
“…In Persian context, researchers (Golchi, 2012;Serraj & Noordin, 2013;Moghadam & Ghanizadeh, 2015) carried out studies in order to explore the relationship between FL listening anxiety level and FL listening comprehension strategy use of learners. These studies found that FL listening anxiety and FL listening comprehension strategy use affected each other.…”
Section: Fl Listening Comprehension Strategies and Fl Listening Anxietymentioning
confidence: 99%